Handbuch Minnereden - Klingner, Jacob; Lieb, Ludger (de Gruyter, 2013)
Late medieval German literature is crucial in the development of modern discourse about love, eroticism, and sexuality. The approximately 600 so-called 'Minnereden' are the most extensive group of texts from this period. But until now they have received only limited attention. This new handbook offers for the first time a comprehensive summary and a manuscript bibliography for each 'Minnerede', as well as a complete index, making it a new and indispensable tool for researchers working in philology, history, and anthropology. Ludger Lieb and Jacob Klingner, Ruprecht-Karls-Universität Heidelberg, Germany.